Lopinavir/ritonavir as part of schemes of HAARt in HIV-positive pregnant women and women of reproductive age: the dynamics of clinical and immunological and virological indicators - A. B. Konkova-Reidman; O. L. Ruhtina; Yu. I. Bulankov (Журнал инфектологии)
The paper presents the results of an open randomized comparative study of the clinical, immunological and virological efficacy of regimens of HAART, including lopinavir/ritonavir (LPV/RTV – “Kaletra”, Abbvie) pregnant women (n= 104) women and women of reproductive age (n=50) c HIV infection. The incidence of adverse events requiring change therapeutic scheme with the inclusion of LPV/RTV did not exceed 2% in both study groups and did not differ statistically. Despite the fact that in the comparison group women significantly differed more advanced stage of the disease, more severe immunosuppression and high activity of viral replication, HAART using LPV/RTV in this group after four weeks of its implementation was significantly better than in the group of women who received the same therapy on a background of pregnancy. Pharmacokinetics of antiviral drugs during pregnancy may require dose increase in order to achieve more rapid virological response and reduce the risk of vertical transmission of HIV from mother to child.